Efektivitas Paenibacillus polymyxa dan Pseudomonas fluorescens dalam Pengendalian Penyakit Hawar Daun (Helminthosporium turcicum) pada Tanaman Jagung (Zea mays L.) - Nurlaela Tuszahrohmi; Ugik Romadi; Irianti Kurniasari (Universitas Trunojoyo Madura, 2019)
Leaf blight caused by fungi Helminthosporium turcicum is an important disease in Indonesia because of the loss of up to 50%. The use of chemical fungicides continuously has a negative impact on humans and the environment. One of the save and environmentally friendly controls is biological control based on antagonistic microorganisms. This study aims to determine the effectiveness of the biological agents Paenibacillus polymyxa and Pseudomonas fluorescens in the controlling of leaf blight in maize. Randomized Block Design used in this research consist of five treatments and each treatment consist of five replications. The treatment consist of P0 is control, P1 is P.polymyxa 10ml L-1, P2 isP.fluorescens 10ml L-1, P3 is P.polymyxa dan P.fluorescens 10ml L-1, P4 is propineb fungicide 70%. The data were analyzed using analysis of variance, if there were significant followed by Duncan test at 5% level. The results showed that P.polymyxa effective reduce leaf blight in maize by 99,89%, besides that P. polymyxa was able to increase plant height and number of leaves significantly compared to controls.